THE INFLUENCE WAREHOUSE LOCATION, TRANSPORTATION, AND INVENTORY ON DISTRIBUTION PERFORMANCE LOGISTICS IN PERUM BULOG BRANCH OFFICE MADIUN - Rahmawati, Nurul (Journal of Economic and Economic Policy, 2024)
Objective: This study examines the influence of warehouse location, transportation, and inventory on logistics distribution performance at Perum BULOG Madiun Branch, focusing on identifying key factors impacting operational efficiency in rice distribution. Methods: A quantitative approach was employed using a survey method. Data were collected via an online questionnaire distributed to 30 employees at the Perum BULOG Madiun Branch. The responses were analyzed using statistical techniques with SPSS Version 26 software to assess the individual and combined effects of the variables on logistics distribution performance. Results: The findings reveal that, individually, warehouse location and transportation have no significant effect on logistics distribution performance, while inventory has a significant positive influence. Simultaneously, all three variables—warehouse location, transportation, and inventory—contribute positively to logistics distribution performance, explaining 87% of the variation. The remaining 13% is attributed to other factors not included in the study. Novelty: This research provides critical insights into the specific factors affecting logistics distribution within a state-owned enterprise. By highlighting the dominant role of inventory management, the study offers actionable recommendations for improving operational efficiency and bridging the supply-demand gap in rice distribution. This research enhances the understanding of logistics performance determinants in public-sector organizations.